Female infertility and dietary antioxidant index (DAI); a case-control study - Roya Kabodmehri; Fatemeh Sadat Hashemi Javaheri; Farkhondeh Alami; Zahra Mahmoudi; Arezoo Amjadi; Zahra Saeedirad; Saeed Omidi; Shiva Sadeghi; Mohadeseh Sadat Mousavi Hoseini; Zahra Mohamadiyan; Zahra Salimi; Hanieh Shafaei; et al. (BMC, 2023)
Abstract Background Adequate intake of natural antioxidants may improve female fertility. The aim of this study was to examine the link between female infertility and dietary antioxidant index (DAI). Methods This case-control study was conducted on 125 women with recently diagnosis of reduced ovarian reserves (AMH < 1.1) as the case group and 125 women with normal ovarian reserve as the control group in Rasht, Iran. The amount of food intake was assessed using the food frequency questionnaire (FFQ) and the DAI was calculated to estimate the antioxidant capacity of the diet. Results Regarding dietary intake, the infertile women had a lower intake of potassium (2789.25 ± 777 vs. 2593.68 ± 443 mg/d, P = 0.02), magnesium (204.12 ± 66 vs. 189.73 ± 34 mg/d, P = 0.03), copper (0.93 ± 0.40 vs. 0.82 ± 0.20 mg/d, P < 0.01), vitamin C (133.99 ± 46 vs. 122.62 ± 24 mg/d, P = 0.02), and fiber (14.53 ± 3 vs. 13.44 ± 2 g/d, P < 0.05), and a higher intake of cholesterol (205.61 ± 58 vs. 227.02 ± 46 mg/d, P < 0.01) than the control group (All P < 0.05). The DAI was negatively associated with infertility (OR: 0.94, CI 95%: 0.88-0.97, P = 0.03). The association remained significant after adjustments for age, BMI, the underlying diseases, fertility frequency, IVF failure, and calorie intake. Conclusion Following an antioxidant-rich diet may reduce the risk of infertility. More longitudinal studies are warranted to confirm these results and discover the underlying mechanisms.